2018
DOI: 10.1016/j.syapm.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The first world swimming championships of roseobacters—Phylogenomic insights into an exceptional motility phenotype

Abstract: Many marine Alphaproteobacteria of the Roseobacter group show a characteristic swim-or-stick lifestyle, for which motility is a crucial trait. Three phylogenetically distinct flagellar gene clusters (FGCs) have been identified in Rhodobacteraceae that have been named fla1, fla2 and fla3 according to their relative abundance. In addition to the flagellar-dependent swimming and swarming motility, pilus-dependent twitching mediates bacterial locomotion. Furthermore, filament independent modes of motility, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The second luxI gene in S. pseudonitzschiae F5 likely produces one or more other AHL molecules that we were not able to characterize due to the limitation of AHL mass spectrometry standards. As mentioned before, S. pseudonitzschiae F5 displayed a dendritic motility phenotype, which is absent in most roseobacters (Bartling et al ., 2018). It is not clear what ecological advantage dendritic motility have on bacteria like S. pseudonitzschiae .…”
Section: Resultsmentioning
confidence: 99%
“…The second luxI gene in S. pseudonitzschiae F5 likely produces one or more other AHL molecules that we were not able to characterize due to the limitation of AHL mass spectrometry standards. As mentioned before, S. pseudonitzschiae F5 displayed a dendritic motility phenotype, which is absent in most roseobacters (Bartling et al ., 2018). It is not clear what ecological advantage dendritic motility have on bacteria like S. pseudonitzschiae .…”
Section: Resultsmentioning
confidence: 99%
“…pseudonitzschiae F5 likely produces one or more other AHL molecules that we were not able to characterize due to the limitation of AHL mass spectrometry standards. As mentioned before, S. pseudonitzschiae F5 displayed a dendritic motility phenotype, which is absent in most roseobacters (Bartling et al, 2018 Interestingly, two additional S. pseudonitzschiae strains displayed this phenotype previously (Bartling et al, 2018), indicating this phenotype is common in this species for unknown reasons.…”
Section: Qs Gene Homology and Organization In The Roseobacter Groupmentioning
confidence: 65%
“…To the authors' knowledge fluid-filled colony protrusions have not been reported previously for any mycobacteria or gram positive bacteria. The closest examples in the literature are some strains of Roseobacters (gram negative), which can form liquid channels, but the mechanism for this phenomenon has not been analysed (Bartling et al, 2018).…”
Section: Digitate Colonies Of Mycobacterium Smegmatis Have Liquid Filmentioning
confidence: 99%
“…Additionally water put onto an agar surface dissipates, even without the action of surfactant, so fluid must be being trapped within the protrusions to prevent it dissipating (Jain et al, 1991). Liquid channels have been seen in several motile Rhodobacteraceae strains (aquatic α-Proteobacteria) but the mechanism for their formation has not been investigated (Bartling et al, 2018). The structure of the colony with a liquid core enclosed by biofilm appears to be unique.…”
Section: Mycobacterium Smegmatis Digitate Colony Structure and How Itmentioning
confidence: 99%